Pengaruh Akuntabilitas dan Transparansi Lembaga Zakat Terhadap Tingkat Kepercayaan Muzakki Dalam Membayar Zakat Di Baitul Mal Kota Banda Aceh - Cut Delsie Hasrina; Yusri Yusri; Dwi Rianda Agusti Sy Sy (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
To increase the potential of zakat at Baitul Mal Kota Banda Aceh then transparency should be prioritized in all aspects. This is important because if it increases then the level of trust muzakki also increased so that will create the desire to pay zakat. This research using purposive sampling method. The data used in the form of primary data by using questionnaires to 50 respondents from 492 muzakki at Baitul Mal Kota Banda Aceh. The methot of data processing is multiple regression SPSS 20.00 for windows program. The results of this study indicate that the variable accountability (X1) has a significant effect on the level of trust muzakki (Y), which is equal to 0.011. The result can be proved by ttest> ttable (2.732> 1.694). The variable transparency of zakatt institutions (X2) has no significant effect on the level of trust muzakki (Y), which is equal to 0.113. This can be proved by ttest <ttabel (1.633 <1.694) with significant <0.05. Furthermore, simultaneously the variable of accountability (X1) and zakat institution transparency (X2) have an effect on muzakki level trustl (Y), it is because Ftest> Ftable (16.414> 3.46).